2022
DOI: 10.1155/2022/8587273
|View full text |Cite
|
Sign up to set email alerts
|

DCAF12 and HSPA1A May Serve as Potential Diagnostic Biomarkers for Myasthenia Gravis

Abstract: Background. Myasthenia gravis (MG) is an autoimmune disease that severely affects the life quality of patients. This study explores the differences in immune cell types between MG and healthy control and the role of immune-related genes in the diagnosis of MG. Methods. The GSE85452 dataset was downloaded from the Gene Expression Omnibus (GEO) database and analyzed using the limma package to determine differentially expressed genes (DEGs) between patients with MG and the control group. Differentially expressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
2
0
1
Order By: Relevance
“…The literature [26] showed in newly diagnosed multiple myeloma NK cells are shifted towards CD56bright NK cells which exhibits selective loss of cytokine production. What's more, CD56bright NK cells secreted interferon-γ, tumor necrosis factor-α to regulate immune system [27]. So, we inferred that LINC01234 depressed NK CD56bright cells, leading to faster progression to a more advanced UCEC clinical stage.…”
Section: Discussionmentioning
confidence: 85%
“…The literature [26] showed in newly diagnosed multiple myeloma NK cells are shifted towards CD56bright NK cells which exhibits selective loss of cytokine production. What's more, CD56bright NK cells secreted interferon-γ, tumor necrosis factor-α to regulate immune system [27]. So, we inferred that LINC01234 depressed NK CD56bright cells, leading to faster progression to a more advanced UCEC clinical stage.…”
Section: Discussionmentioning
confidence: 85%
“…A study revealed that the ROC result of HSPA1A mRNA in the diagnosis of myasthenia gravis was 0.830 [ 46 ]. Zhang et al confirmed that HSPA8 as a potential serum biomarker for distinguishing renal cell carcinoma from benign urologic disease with ROC area under the curve (AUC) of 0.86 [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dentre os diferentes membros pertences à família das Hsp70 humanas, uma das isoformas mais comumente estudada é a HspA1A (DAUGAARD, M., ROHDE, M., JÄÄTTELÄ, M., 2007;RADONS, J., 2016). Esta atua como um importante constituinte da rede celular das chaperonas moleculares e provedoras de folding dentro das células (KIM et al, 2015), além de corresponder a principal proteína citosólica estudada com importante papel em doenças neurodegenerativas, bem como alta expressão sob condições de estresse térmico (SÕTI et al, 2005;BORGES, J. C., RAMOS, C. H. I., 2006;KASIOUMI et al, 2019;SULZBACHER et al, 2020;NONG et al, 2022;SMULDERS et al, 2022).…”
Section: Hspa1aunclassified